Ações de desenvolvimento profissional de professores da educação superior no Brasil e na Argentina: um estudo comparado entre o GIZ (UFMG) e as assessorias pedagógicas (UBA) - Juliana Santos da Conceição (2020)
This thesis aims to analyze and compare the formative actions of professional development carried out in public universities of college education in Brazil and Argentina. Specifically, we intend to characterize the formative actions in these universities; identify and analyze the conceptions of teacher training that guide these actions and the perceptions of the participants involved (program coordinators, teacher trainers and participating teachers). As a theoretical contribution, we work the concept of teacher professional development through the studies of Imbernón, Day and Diniz-Pereira; we went through studies on pedagogy and university teaching; we brought Bourdieu's concept of field to discuss scientific capital and 'pedagogical capital' in the university field. The methodological approach adopts a qualitative approach linked to the principles of comparative research. Our investigation field consisted of the analysis of two formative experiences developed by college education institutions: in Brazil, our object of study was the PerCurso Docente offered by GIZ, UFMG's Directorate of Innovation and Teaching Methodologies; in Argentina, we analyzed the formative course called Carrera Docente at the Faculties Pharmacy and Biochemistry, Dentistry and Law, all of the University of Buenos Aires. As data collection instrument we used observations, document analysis, questionnaire and semi-structured interviews (21 interviews in Brazil and 14 in Argentina). We based on the principles of thematic analysis proposed by Minayo (2010) and used, as theoretical variables, the analysis indicators of teacher education programs proposed by Cunha (2014). We conclude that there is no single formative way to go, the paths are multiple and have direct relation with the field’s contexts in which each action is inserted, as well as the culture, working conditions, political contexts and theoretical bases. All of these elements provide the resources needed to analyze each experiment. The findings of this academic investigation responds our initial hypothesis that understood that teacher professional development in Brazil and Argentina would be influenced by distinct characteristics, since the career composition is influenced by the academic culture and the autonomy constitution process in both universities studied, revealed by the power relations established there. We clearly saw that power relations established in both universitary fields are driven by this field’s agents who give different values to different capitals. Still according to our hypothesis, the formative actions offered by the institutions in both countries reveal similar conceptions of formation, but with unique valuations for the teaching career constitution and its professional development. We believe that the great contribution that this research brings to pedagogy field and university teaching focuses on our effort to discuss professional development actions in a broader perspective, by analyzing these actions from the perspective of the universitary field where each of these actions is inserted. We argue for the existence of another capital within this field, other than scientific capital, already widely discussed by Bourdieu, we believe that, within another configuration of the university field, “pedagogical capital” may occupy a prestigious place within it.